Development and environmental validation of a compact EDFA with integrated LNA+HPA for satellite optical communications - Carrasco-Casado, Alberto; Shiratama, Koichi; Kolev, Dimitar; Tsuji, Hiroyuki; Toyoshima, Morio (Frontiers in Physics, 2025)
The Japanese National Institute of Information and Communications Technology (NICT) plans to launch a 6U CubeSat into Low Earth Orbit (LEO) during the Japanese fiscal year 2025. The primary payload for this mission is CubeSOTA (CubeSat’s Small Optical TrAnsponder), a miniaturized free-space optical communication terminal currently under development. A key component of this terminal is the optical amplifier, which must provide high transmission gain to overcome the significant free-space losses caused by the long distances involved in space communications. Additionally, to enable seamless integration into communication networks, the optical amplifier must support bidirectional communications. To achieve this, the amplifier incorporates a 2-in-1 design, integrating a high-power amplifier (HPA) for the transmission path and a low-noise amplifier (LNA) for the reception path. This paper presents the key features of this recently developed optical amplifier and its space qualification process, which is essential before its integration into the CubeSOTA terminal for launch. The developed amplifier features a 9 × 9.5 cm footprint for compatibility with the CubeSat standard, a reduced height of 3.6 cm and mass of 0.56 kg, while the HPA can deliver an output exceeding 2 W and the LNA is optimized for Doppler compensation and low noise with a noise figure below 4.5 dB. The environmental testing focuses on the amplifier’s most critical features, namely, its performance across varying temperature conditions in a vacuum and its power consumption under different operation modes.